1995
DOI: 10.1039/ft9959102041
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of carbon dioxide, sulfur dioxide and water vapour by MCM-41, a model mesoporous adsorbent

Abstract: Adsorption isotherms of carbon dioxide, sulfur dioxide and water vapour have been determined on a well characterized sample of MCM-41. The shape of the carbon dioxide isotherm (at 195 K) is similar to that given by mesoporous hydroxylated silica, whereas the water isotherm (at 303 K) is of Type V in the IUPAC classification and its shape is therefore indicative of a more hydrophobic behaviour. lsosteric enthalpies of adsorption, calculated from the sulfur dioxide isotherms (at 254 and 273 K), reveal strong en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 8 publications
6
61
0
Order By: Relevance
“…glass, and -13.7 ± 3.0 for andesite glass. The value for dacite glass is close to the −26 kJ/mol reported for SO 2 adsorption on MCM-41, a mesoporous alumosilicate material, at high surface coverage (Branton et al 1995).…”
Section: A Multiple Regression Model Of So 2 Adsorptionsupporting
confidence: 63%
“…glass, and -13.7 ± 3.0 for andesite glass. The value for dacite glass is close to the −26 kJ/mol reported for SO 2 adsorption on MCM-41, a mesoporous alumosilicate material, at high surface coverage (Branton et al 1995).…”
Section: A Multiple Regression Model Of So 2 Adsorptionsupporting
confidence: 63%
“…On average, the resulting values, N w = 31.1 AE 1 nm À3 , are about 7% smaller than the number density of bulk water (33.4 nm À3 at 20 1C), but no systematic dependence of the density on the pore width can be detected. In other studies 29,32 the density of water in the pores of MCM-41 was reported to be 11-12% smaller than that of bulk water.…”
Section: Water Sorption Isothermsmentioning
confidence: 84%
“…16 This critical pore size is smaller for water than for any other adsorbate investigated so far, including N 2 , O 2 , Ar, or CO 2 . 16,37,39 In some of these studies, it has been suggested that the width of the hysteresis loop, or the critical pore diameter, is determined by the molecular size of the adsorbate. 37 The density of the liquid plug can be computed from the data in Fig.…”
mentioning
confidence: 99%